Exogenous normal lymph alleviates lipopolysaccharide-induced acute lung injury through lessening the adhesion molecules - Zhang,Li-li (2014)
PURPOSE: To evaluate the role of exogenous normal lymph (ENL) on lipopolysaccharide (LPS)-induced acute lung injury (ALI) in rats.METHODS:ALI was induced by the jugular vein injection of LPS (iv, 15 mg/kg) in rats of the LPS and LPS+ENL groups within 15 min, then, ENL without cell components (5 ml/kg) was infused at the speed of 0.5 ml per minute in the LPS+ENL group, the same amount of saline was administered in the LPS group. The rats in the sham group received the same surgical procedure and saline. The histomorphology and the levels of P-selectin, intercellular adhesion molecule-1 (ICAM-1), myeloperoxidase (MPO) in pulmonary tissue were assessed.RESULTS: LPS induced pulmonary injury as well as increased the wet/dry weight ratio (W/D) and the levels of P-selectin, ICAM-1, and MPO in pulmonary tissues. These deleterious effects of LPS were significantly ameliorated by ENL treatment.CONCLUSION: Exogenous normal lymph could markedly alleviate the acute lung injury induced by lipopolysaccharide, and its effects might be related to lessening the adhesion molecules.